Spatial Effect of Economic Growth Targets on CO2 Emissions: Evidence From Prefectural-Level Cities in China - Ge, Tao; Ma, Li; Wang, Cang (Frontiers in Environmental Science, 2022)
Since the GDP-oriented evaluation system was introduced in China, setting ambitious economic growth targets has become a norm for governments at all levels, which promotes rapid economic growth but also causes serious carbon emissions. To achieve high-quality sustainable development, a key issue is to optimize the role of economic growth targets by studying their impact on the environment. In this context, this paper employs the spatial Durbin model to investigate the impact of economic growth targets on CO2 emissions based on panel data of 285 prefecture-level and above cities in China during the period 2005–2018. The results show that economic growth targets have a negative effect and a positive impact on CO2 emissions locally and adjacently, respectively, although the spillover effect decays rapidly in space. Heterogeneity analysis suggests that the adverse impact of economic growth targets on carbon emission reduction varies by city, and is generally lower in cities that have more abundant human, financial, and material resources. Additionally, the mechanistic analysis reveals that fiscal decentralization and environmental decentralization are the key channels through which economic growth targets impact carbon emissions, serving as a mediating and masking effect in local and adjacent regions, respectively. Based on the above findings, this study provides policy recommendations for the government to reduce carbon emissions by optimizing the target management system.